2020
DOI: 10.1371/journal.pone.0240310
|View full text |Cite
|
Sign up to set email alerts
|

Automated dry thawing of cryopreserved haematopoietic cells is not adversely influenced by cryostorage time, patient age or gender

Abstract: Cell therapies are becoming increasingly widely used, and their production and cryopreservation should take place under tightly controlled GMP conditions, with minimal batch-to-batch variation. One potential source of variation is in the thawing of cryopreserved samples, typically carried out in water baths. This study looks at an alternative, dry thawing, to minimise variability in the thawing of a cryopreserved cell therapy, and compares the cellular outcome on thaw. Factors such as storage time, patient age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…Specifically, it was found that an apparent >90% viable population 1 h post-thaw decreased to less than half that (between 20–40%) by 24 h post-thaw following hHPC cryopreservation using traditional culture media with 5 or 10% DMSO ( Figure 1 ). This finding was consistent with previous reports that describe HPC and/or HSC post-thaw viability to range between 40 and 60% of pre-freeze controls with varying cryopreservation media formulations and cryoprotective agents, including 10% DMSO [ 64 , 88 , 95 , 96 , 97 , 98 , 99 , 100 ]. When samples were cryopreserved using Unisol™, overall hHPC viability at 24 h post-thaw increased to 60–65% depending on the DMSO concentration ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, it was found that an apparent >90% viable population 1 h post-thaw decreased to less than half that (between 20–40%) by 24 h post-thaw following hHPC cryopreservation using traditional culture media with 5 or 10% DMSO ( Figure 1 ). This finding was consistent with previous reports that describe HPC and/or HSC post-thaw viability to range between 40 and 60% of pre-freeze controls with varying cryopreservation media formulations and cryoprotective agents, including 10% DMSO [ 64 , 88 , 95 , 96 , 97 , 98 , 99 , 100 ]. When samples were cryopreserved using Unisol™, overall hHPC viability at 24 h post-thaw increased to 60–65% depending on the DMSO concentration ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…To this end, initial observations of the CD34+ cells within the surviving HPC samples suggest a similar % fraction between samples cryopreserved in media or Unisol + DMSO and cultured in recovery media with or without n-acetyl cysteine supplementation. While preliminary, these initial findings are consistent with previous reports [ 51 , 88 , 95 , 96 , 97 , 98 , 99 , 100 , 101 ], and suggest that post-thaw conditioning may provide for increased recovery of total viable cells as well as maintenance of the CD34+ subpopulation, correlating to a higher number of viable CD34+ cells post-thaw. While encouraging, these observations are highly preliminary; therefore, further investigation must be completed prior to drawing any definitive conclusions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Otherwise, it could take up to three weeks [9]. It should be noted, however, that fast thawing is not necessarily associated with improved post-thaw recovery [13].…”
Section: Optimizing the Process Of Thawing Cryopreserved Cellsmentioning
confidence: 99%